2020
DOI: 10.35232/estudamhsd.701164
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mental Disorders and Related Factors of Students on Health Sciences Campus

Abstract: Üniversite öğrencilerinin mevcut ruhsal bozukluk semptomlarının ve bunların sosyodemografik faktörler ile olası ilişkilerinin belirlenmesi amaçlanmıştır. Kesitsel tipteki araştırmanın evrenini 2018-2019 eğitim-öğretim yılında üniversitede öğrenim görmekte olan lisans öğrencileri oluşturmaktır. Sınıf seviyesine göre tabakalandırılarak her fakülteden öğrenci sayısıyla orantılı olacak şekilde tabakalı rastgele örneklem yöntemi ile 814 katılımcı ile çalışmamız yürütülmüştür. Veriler gözlem altında katılımcılar tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…gender in some studies (24,25), it is higher in females in some studies (26,27). In this study, the level of depression was also found to be higher in females than males.…”
Section: While the Level Of Depression Does Not Differ Regardingsupporting
confidence: 57%
“…gender in some studies (24,25), it is higher in females in some studies (26,27). In this study, the level of depression was also found to be higher in females than males.…”
Section: While the Level Of Depression Does Not Differ Regardingsupporting
confidence: 57%